Reflection on social aspects in Pahang folktales - Azmi, Azie; Nik Muhamad Affendi, Nik Rafidah; Sujud, Arba’ie (Human Resources Management Academic Research Society (HRMARS), 2024)
Folktales are a form of traditional literature that play an important role in conveying the thoughts and values of past societies to present-day communities. Therefore, this study aims to identify and analyze the social aspects in Pahang folktales. To achieve this objective, the study employs a societal approachbased on the Malay Methodology Theory by Hashim Awang (1993). A total of 11 Pahang folktales contained in the text "Himpunan 366 Cerita Rakyat Malaysia," edited by Othman Puteh and Aripin Said(2010), are analyzed in this study. The results indicate that traditional Malay society skillfully blendedstories to illustrate the effects and consequences of being an unwise community. The messages conveyed also have a significant impact on society.